Phenotypic variability in cases with CACNA1A mutation - Bozkaya-Yilmaz, Sema; Olgac-Dundar, Nihal; Aliyeva, Nargiz; Ersen, Atilla; Gencpinar, Pinar; Gungor, Mesut; Kara, Bulent (Springer, 2025)
The purpose of this study was to enhance understanding of CACNA1A gene variants by elucidating the clinical profiles of patients with different variants. The overlapping features and varying phenotypic characteristics of these neurological disorders pose challenges for clinicians. A data collection form was utilized to gather clinical features, examination details, and treatment information associated with CACNA1A variants. Thirty-one patients were included in the study from 11 different clinics in Turkey. Cases were assessed by comparing their information with existing literature. The study initially included 32 patients from 29 families, with 31 patients meeting the inclusion criteria. Clinical manifestations ranged from congenital onset hypotonia to motor seizures. Within the group of patients, 87% were diagnosed with epilepsy, 61% had neurodevelopmental defects, 32% experienced ataxia, 22% had eye movement problems, 16% suffered from migraines, and 13% had recurrent encephalopathy. Thirty percent of individuals exhibited cerebellar atrophy. A subset of individuals exhibited various forms of cognitive impairment and different kinds of ataxia.Conclusion: CACNA1A variants can lead to structural and functional abnormalities in the Cav2.1 channels, resulting in paroxysmal and/or chronic clinical presentations. The overlapping phenotypes and variable features among family members suggest the influence of environmental factors and modifier genes. A thorough understanding of the range of phenotypic variants and the difficulties encountered by medical professionals is essential for precise diagnosis and efficient treatment approaches in various neurological conditions. Additional research is necessary to clarify the underlying mechanisms that contribute to the various presentations of these variants. What is known:center dot Variants in the CACNA1A gene disrupt calcium signaling, thereby impacting fundamental developmental processes such as neuronal differentiation, migration, and synapse formation.center dot Variants in the CACNA1A can lead to neurodevelopmental disorders characterized by intellectual disability, learning difficulties, memory challenges, and problems in social interaction.What is new:center dot Instances of intrafamilial variability in CACNA1A variants have been identified, with differing clinical manifestations exhibited by affected family members.center dot Incomplete penetrance is a phenomenon that may occur, as neurodevelopmental or neuropsychiatric findings are not exhibited by some patients with CACNA1A variants.
Keywords: CACNA1A; Genetic; Epilepsy; Neurodevelopmental disorder